Are maternal hemodynamic indices markers of fetal growth restriction in pregnancies with a small‐for‐gestational‐age fetus?. (3rd February 2020) - Perry, H.; Lehmann, H.; Mantovani, E.; Thilaganathan, B.; Khalil, A.
ABSTRACT: Objective: Pregnancies complicated by fetal growth restriction (FGR) have a worse outcome than those with a small‐for‐gestational‐age (SGA) fetus. There is increasing evidence of a maternal cardiovascular role in the pathophysiology of FGR. We aimed to compare maternal hemodynamic indices between pregnancies complicated by FGR and those delivering a SGA neonate, using a non‐invasive device. Methods: This was a prospective study of normotensive pregnancies complicated by FGR (defined as estimated fetal weight (EFW) < 3 rd centile or Doppler evidence of impaired placental‐fetal blood flow), those with a SGA fetus (defined as EFW < 10 th centile) and control pregnancies with an appropriately grown fetus. Assessment of maternal hemodynamics (heart rate (HR), cardiac output (CO), mean arterial pressure (MAP), systemic vascular resistance (SVR) and stroke volume) was performed using a non‐invasive device (USCOM‐1A®). Uterine artery (UtA) pulsatility index (PI) was measured using transabdominal ultrasound. Hemodynamic variables that are affected by gestational age and maternal characteristics were corrected for using device‐specific reference ranges. Comparison between groups was performed using the chi‐square test or the Mann–Whitney U ‐test, as appropriate. Results: A total of 102 FGR, 64 SGA and 401 control pregnancies, with a median gestational age of 36 weeks, were included in the analysis. Women with a pregnancy complicated by FGR and those with a SGA fetus were shorter and weighed less than did controls. Compared with controls, the FGR group had significantly lower median maternal HR (80 beats per min (bpm) vs 85 bpm; P  = 0.001) and CO multiples of the median (MoM; 0.91 vs 0.98; P  = 0.003), and higher median maternal MAP (90 mmHg vs 87 mmHg; P  = 0.040), SVR MoM (1.2 vs 1.0; P  < 0.001) and UtA‐PI MoM (1.1 vs 0.96; P  < 0.001), but there was no significant difference in stroke volume MoM (1.0 vs 0.98; P  = 0.647). Compared with the SGA group, the FGR group had a significantly lower median HR (80 bpm vs 87 bpm; P  = 0.022), and higher median maternal MAP (90 mmHg vs 85 mmHg; P  = 0.025), SVR MoM (1.2 vs 1.0; P  = 0.002) and UtA‐PI MoM (1.1 vs 0.98; P  = 0.005), but there was no significant difference in CO MoM (0.91 vs 0.96; P  = 0.092) or stroke volume MoM (1.0 vs 1.0; P  = 0.806). There were no significant differences in adjusted maternal hemodynamic indices between the SGA group and controls. Conclusion: Pregnancies complicated by FGR presented with impaired maternal hemodynamic function, as evidenced by lower HR and CO, as well as higher MAP, SVR and UtA resistance. Pregnancies delivering a SGA neonate, without evidence of FGR, had normal maternal hemodynamic function. Maternal hemodynamic indices may therefore be of value in distinguishing FGR from SGA pregnancies. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.